1975
DOI: 10.6028/nbs.ir.75-740
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric polymer transducer for impact pressure measurement

Abstract: The development and calibration efforts described in this report are exploratory in nature and are intended to serve as a basis for further work. The measurement results reported are derived from a statistically small number of test transducers, and the conclusions that may be drawn are therefore tentative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Piezoelectric PVDF film is a type of piezoelectric polymer that has been widely used for many applications such as sensor or energy harvesting due to their good sensitivity, flexibility, mechanical strength and displacement [1][2][3][4][5][6][7][8][9]. Generally, there are five main procedures in making piezoelectric PVDF film including: stretching PVDF films, depositing electrode onto PVDF surface, poling process, wiring in copper plate, and laminating with plastic.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric PVDF film is a type of piezoelectric polymer that has been widely used for many applications such as sensor or energy harvesting due to their good sensitivity, flexibility, mechanical strength and displacement [1][2][3][4][5][6][7][8][9]. Generally, there are five main procedures in making piezoelectric PVDF film including: stretching PVDF films, depositing electrode onto PVDF surface, poling process, wiring in copper plate, and laminating with plastic.…”
Section: Introductionmentioning
confidence: 99%
“…Test results showed that a linear relationship can be established for both cases. 7) The linear relationship between input stress and corrected gage output holds for the gage whether it is placed on a concrete pedestal and backfilled by soil, or embedded in soil to simulate a free field condition. Therefore, the gage needs only to be tested under either condition to establish the relationship.…”
Section: Presentation Interpretation and Discussion Of Test Resultsmentioning
confidence: 99%
“…The polymer gage has been used in several studies to measure dynamic pressure developed by impact loads. In a 1975 study by DeReggi [7], the polymer gage was designed, constructed, and calibrated for recording pressure transients developed over the interface between two bodies as a result of impact. The measurement of interface pressure is of interest in studying injuries sustained in vehicular crashes.…”
Section: Pressure Measurementmentioning
confidence: 99%
See 2 more Smart Citations